UPAYA GURU DALAM MENINGKATKAN SIKAP HORMAT ANAK USIA DINI DI TK PEMBINA - Audita, Almiati; Aunurrahman, Aunurrahman; Amalia, Annisa (Universitas Tanjungpura, 2024)
This study aims to describe the teacher's efforts to improve the attitude of respect for early childhood in the learning process at the Kindergarten Trustees of Sungai Alloy Village, Teluk Batang District. The research method used is qualitative. The subjects in this study were 2 teachers. Data collection techniques used are observation, interviews, and documentation. The data analysis carried out was data collection, data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses triangulation. The results of this study show that: 1. The teacher's efforts to increase children's respect in using polite language when communicating with the teacher, the effort that the teacher makes is that the teacher welcomes the child and greets and invites children to communicate in polite language, before starting the learning activity the teacher asks to children and communicate using polite language. 2. The teacher's efforts to increase the child's respect when listening to advice or directions from the teacher, the efforts made by the teacher are the teacher giving advice or directions to the child after the ceremony, then after the ceremony the child will shake hands with the teacher. 3. The teacher's efforts to increase children's respect when interacting with peers, the efforts made by the teacher are that the teacher gives children toys to assemble blocks, and children color pictures. The conclusion from this study is that the teacher's efforts to increase children's respect have been carried out well for children in the TK Pembina Sungai Alloy Village, Teluk Batang District, Kayong Utara Regency.